The Impact of Workplace Wellbeing on Job Performance with Work Engagement as a Mediating Variable - Andriani Pratiwi, Endah; Griselfa Davina, Sylvia (Riviera Publishing, 2023)
In an increasingly complex and competitive world of work, organisations need to pay attention to the workplace well-being of employees. Workplace well-being includes job satisfaction, work-life balance, social support and a healthy work environment. High work well-being can have a positive impact on employee performance. This study aimed to examine the impact of workplace well-being on job performance, with work engagement as a mediating variable. This research uses quantitative research methods. Data was collected through a literature study and a survey using a questionnaire. The population of this research is 1,800 Production Division employees at PT. Leading Garment Industries Bandung was selected using a purposive sampling technique. The collected data were analysed using statistical analysis techniques. The results showed that workplace well-being did not affect job performance. At the same time, the work engagement variable had a positive and significant effect. In addition, work engagement positively and significantly affects job performance. Whereas in the mediating variable, there is an indirect effect between workplace well-being on job performance which is mediated by work engagement, and there is no direct effect between workplace well-being on job performance.